Chemoselective Zinc/HCl Reduction of Halogenated β-Nitrostyrenes: Synthesis of Halogenated Dopamine Analogues - Maresh, Justin J.; Ralko, Arthur A.; Speltz, Tom E.; Burke, James L.; Murphy, Casey M.; Gaskell, Zachary; Girel, JoAnn K.; Terranova, Erin; Richtscheidt, Conrad; Krzeszowiec, Mark (Synlett, 2014)
A detailed account regarding the synthesis of 2- and 5-halogenated dopamine is given. The key step is a chemoselective reduction of a nitrostyrene by Zn/HCl at 0 °C. These conditions represent a simple, low-cost alternative to reduction by water-sensitive hydride donors and two-step procedures. Under these conditions, aryl fluoride, chloride, and bromide groups are stable. However, iodine undergoes significant reductive dehalogenation.
Keywords: reduction; nitroalkene; zinc; dopamine; dehalogenation